Feasibility of typha latifolia for high salinity effluent treatment in constructed wetlands for integration in resource management systems - Jesus, J. M. (2014)
High salinity wastewaters have limited treatment options due to the occurrence of salt inhibition in conventional biological treatments. Using recirculating marine aquaculture effluents as a case study, this work explored the use of Constructed Wetlands as a treatment option for nutrient and salt loads reduction. Three different substrateswere tested for nutrient adsorption, of which expanded clay performed better. This substrate adsorbed 0.31 mg kg−1 of NH4 +−N and 5.60 mg kg−1 of PO4 3−−P and 6.9 mg kg−1 dissolved salts after 7 days of contact. Microcosms with Typha latifolia planted in expanded clay and irrigated with aquaculture wastewater (salinity 2.4%, 7 days hydraulic retention time, for 4 weeks), were able to remove 94%NH4 +−N(inlet 0.25±0.13 mg L−1), 78%NO2 −−N(inlet 0.78±0.62 mg L−1), 46% NO3 −−N (inlet 18.83 ± 8.93 mg L−1) whereas PO4 3−−P was not detected (inlet 1.41 ± 0.21 mg L−1). Maximum salinity reductions of 52% were observed. Despite some growth inhibition, plants remained viable, with 94% survival rate. Daily treatment dynamics studies revealed rapid PO4 3−−P adsorption, unbalancing the N:P ratio and possibly affecting plant development. An integrated treatment approach, coupled with biomass valorization, is suggested to provide optimal resource management possibilities.